Acute limb ischemia of the lower extremity associated with left upper lobe surgery for primary lung cancer - Shigesato Inoue, MD; Sosei Kuma, MD, PhD; Takefumi Ohga, MD, PhD; Keita Tokuishi, MD, PhD; Kan Okabayashi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2018)
Thrombosis formation in the pulmonary vein stump after pulmonary lobectomy has recently been reported to be an extremely rare cause of arterial embolism. We herein report the first case series of acute limb ischemia encountered after video-assisted thoracoscopic left upper lobectomy or left upper division segmentectomy for primary lung cancer. The patients underwent embolectomy, and their perioperative courses were uneventful. It should be recognized that the pulmonary vein stump can cause acute limb ischemia after pulmonary lobectomy. Key words: Multidetector computed tomography, Perioperative, Left upper lobectomy